ANALISA KADAR CO,NO2 DAN SO2 DI KAWASAN INDUSTRI MEDAN DAN KAWASAN NON INDUSTRI DI KOTA MEDAN PADA TAHUN 2013 - Yuliana Ramadhani (Lingkungan dan Kesehatan Kerja, 2014)
Abstract The industrial area is the area that is specified for the industrial area. The total of industries in KIM (Kawasan Industri Medan) as 109 industry. Non-industrial area is a region where people can live and also the testive are in this place can caused air pollution. This research aimed to know the level of CO, NO2, SO2, the speed of wind, temperature, humidity, the total of vehicles and the distance of absorbent pollutans in industrial area and non-industrial area. This research was survey, The object of this research were CO, NO2, and SO2 level in ambient. And the result can be found directly the measure of industrial area and non-industrial area. The result showed that the level of CO was highest in industrial area (17.170 µg/Nm3), meanwhile the level of CO lowest was in non-industrial area (9.160 µg/Nm3). The level of NO2 was highest in industrial area (32,45 µg/Nm3), on the other hand the level of NO2 lowest was non-industrial area (13,05 µg/Nm3). And the level of SO2 highest was in non-industrial area (54,38 µg/Nm3), while the level of SO2 lowest was in  industrial area (47,92 µg/Nm3). Conclusions of this research was the industrial area and non-industrial area did’nt  over the qualities standard of air CO (30.000 µg/Nm), NO2 (400 µg/Nm) and SO2 (900 µg/Nm). We suggestion the manager of industrial to supervising air quality and for the government to increase amount of tree in Medan.